Control and monitoring system of bio-mass weight feeder equipment in Indarung V PT Semen Padang - Dwi Kurniawan, Bintang; Yuhendri, Muldi (Journal of Industrial Automation and Electrical Engineering, 2025)
The Industrial Revolution 4.0 encourages the application of intelligent technologies such as the Internet of Things (IoT) in industrial automation systems to improve efficiency, flexibility, and monitoring accuracy. This study aims to design and implement an IoT-based monitoring system integrated with the Siemens S7-1200 PLC on the biomass weight feeder tool at the Indarung V unit of PT Semen Padang. This system was developed to enable real-time and remote monitoring of equipment conditions, which previously could only be done from a local panel or control room. The design was carried out by combining ladder diagram programming on the TIA Portal and data visualization using Node-RED as an IoT platform. Testing was carried out in the laboratory through three main scenarios, namely variations in induction motor speed, alarm condition simulation, and connectivity testing between PLC, HMI, PC server, and PC client. The test results showed that the system was able to display speed and tool status data accurately with a delay time of less than one second. The indicator alarm successfully detected abnormal conditions and provided visual notifications appropriately. Connectivity between devices was also proven to be stable and synchronous during testing. With these results, this monitoring system is considered effective in supporting digital transformation in the industrial sector, especially in increasing the responsiveness and reliability of monitoring the biomass transportation process, and has the potential to be applied on a wider industrial scale